2004
DOI: 10.1038/ncb1119
|View full text |Cite
|
Sign up to set email alerts
|

FAPPs control Golgi-to-cell-surface membrane traffic by binding to ARF and PtdIns(4)P

Abstract: The molecular mechanisms underlying the formation of carriers trafficking from the Golgi complex to the cell surface are still ill-defined; nevertheless, the involvement of a lipid-based machinery is well established. This includes phosphatidylinositol 4-phosphate (PtdIns(4)P), the precursor for phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P(2)). In yeast, PtdIns(4)P exerts a direct role, however, its mechanism of action and its targets in mammalian cells remain uncharacterized. We have identified two eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
476
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(505 citation statements)
references
References 47 publications
21
476
0
1
Order By: Relevance
“…The most striking effect was a decrease in the number of late Golgi structures, visible for all of the mutants with Sec7p-GFP and FAPPI(PH)-GFP (Figure 4). The FAPPI pleckstrin homology (PH) domain binds specifically to PI(4)P and localizes to the late Golgi in yeast and the trans-Golgi network (TGN) in mammalian cells (Stefan et al, 2002;Godi et al, 2004). The loss of FAPPI-containing structures was rapid, occurring within 15-20 min after shift to the nonpermissive temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking effect was a decrease in the number of late Golgi structures, visible for all of the mutants with Sec7p-GFP and FAPPI(PH)-GFP (Figure 4). The FAPPI pleckstrin homology (PH) domain binds specifically to PI(4)P and localizes to the late Golgi in yeast and the trans-Golgi network (TGN) in mammalian cells (Stefan et al, 2002;Godi et al, 2004). The loss of FAPPI-containing structures was rapid, occurring within 15-20 min after shift to the nonpermissive temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The related PH domains include those from oxysterol binding protein (OSBP), its S. cerevisiae homologs Osh1p and Osh2p, and the Goodpasture antigen binding protein (GPBP). Several studies have shown that the Golgi localization of these PH domains is dependent on the production of PtdIns4P in the Golgi [61][62][63][64], and it was argued that the FAPP1 PH domain is a highly specific PtdIns4P-specific domain that can be used to monitor the distribution of this phosphoinositide in living cells [63,64].…”
Section: Ptdins4p-specific Ph Domainsmentioning
confidence: 99%
“…That PtdIns4P is not exclusively responsible for Golgi targeting of these PH domains was suggested by the finding that Arf1 is also critical for their localization at this site [61,62]. Perhaps more importantly, studies in our own laboratory ( [27] and unpublished data) and those of Levine and Munro [61,65] argue that the FAPP1, OSBP, GPBP, Osh1p and Osh2p PH domains are not PtdIns4P-specific at all in vitro.…”
Section: Ptdins4p-specific Ph Domainsmentioning
confidence: 99%
“…A specific function of sphingolipids on cytosolic surfaces is suggested by the fact that the cytosolic protein FAPP2, which contains a glycolipid binding domain, plays a role in regulating membrane flow between the Golgi and the plasma membrane [49]. Finally, whereas cholesterol is assumed to move passively across and between membranes, this transport appears to be mediated by intricate machineries.…”
Section: Updatementioning
confidence: 99%